Tovomita manauara (Clusiaceae): a new species revealed by fruit morphology and leaf anatomy - Monteiro Nobre, Alexandra; Cardoso Marinho, Lucas; Nunes Cabral, Fernanda; Oreste Demarchi, Layon; Hipólito De Sousa, Juliana (Phytotaxa, 2022)
Herein, we present Tovomita manauara A. Nobre & L. Marinho, a new species of Clusiaceae that is presumably endemic to the Amazonas state, in Brazil. The new species was initially identified as T. caloneura A.C. Sm., which is a morphologically similar and sympatric species. Although the species was based only on vegetative and fruit morphological characteristics, Tovomita manauara can be recognized by the large number of secondary veins (25–36 pairs vs. up to 26 pairs in T. caloneura) and 4-septate, turbinate to napiform fruits (vs. 5-septate and fusiform in T. caloneura). In addition to macromorphology, anatomical characters, such as the secretory canals larger, presence of collenchyma in the petiole, and the absence of druses in the midvein are also helpful for the identification of T. manauara.